El apocalipsis doméstico: El fin del mundo según Jaume Balagueró (Altre Modernità, 2013)
Jaume Balagueró's cinematography is directly connected with Adam Parfrey´s  concept of "Apocalypse Culture". It is a very personal vision of the end of the world in everyday life context. This author´s cinema does not show dystopian environments or collapsing societies or major natural disasters, on the contrary, the apocalypse born  indoors.Balagueró builds his peculiar vision of the end of the world from his fondness for the dark and millenarian spirit. His works address from a gloomy and ugliness aesthetics more rooted in human society such as death, ancestral rites, as something immovable, the pursuit of primal evil as overcoming of conventional religions.This paper aims to analyze the aesthetic, discursive and stylistic constacts that define the Jaume Balagueró´s cinema as apocalypse films, in which converge the classic and modern into what we call the Nova Escola de Barcelona.